2002
DOI: 10.1002/chin.200220291
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Conformational Studies of Oligosaccharides and Glycopeptides: Complementary of NMR, X‐Ray Crystallography, and Molecular Modelling

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Compared to conventional spectroscopic methods, which are hampered by conformational averaging and offer limited structural information, computational methods are a valuable alternative that provide access to discrete conformational states and a broader understanding of the overall energetic landscape. 27 In order to fully assess the implications of deoxygenation, a large compilation of deoxysugar stereoisomers were computationally modeled in this study and a simplified scheme of these structures is provided in Figure 1. An expanded version including all discrete deoxysugar structures modeled (Figures S2 and S3), as well as a comprehensive literature compilation of all synthetic preparative routes and related computational studies (Tables S1 and S2) can be found in the SI.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional spectroscopic methods, which are hampered by conformational averaging and offer limited structural information, computational methods are a valuable alternative that provide access to discrete conformational states and a broader understanding of the overall energetic landscape. 27 In order to fully assess the implications of deoxygenation, a large compilation of deoxysugar stereoisomers were computationally modeled in this study and a simplified scheme of these structures is provided in Figure 1. An expanded version including all discrete deoxysugar structures modeled (Figures S2 and S3), as well as a comprehensive literature compilation of all synthetic preparative routes and related computational studies (Tables S1 and S2) can be found in the SI.…”
Section: Introductionmentioning
confidence: 99%